Association between different screening strategies for SARS‐CoV‐2 and deaths and severe disease in Italy. Issue 4 (14th December 2020) - Mannucci, Edoardo; Silverii, Antonio; Monami, Matteo
Abstract: Background: The WHO recommends testing any suspected person with Severe Acute Respiratory Syndrome CoronaVirus‐2 (SARS‐CoV‐2), in order to limit the spread of the epidemic. In Italy, some Regions opted for extensive testing, whereas others limited tests to selected subjects. To assess the influence of different strategies, we examined the incidence of death and severe cases in Italy. Methods: Data on new cases of SARS‐CoV‐2, number of tests, deaths and admissions to Intensive Care Units (ICU) were retrieved in each Italian Region, from 24 February to 18 March 2020. As an index of different screening strategies, the number of tests/positive test results (P/T) ratio as of 7 March 2020, was considered. The cumulative number of deaths and of new severe cases, between March 23 and 25 was recorded. The association of those two outcomes with the number of P/T ratio was assessed using linear regression models. Results: In the interval between March 23 and 25, recorded deaths (*million inhabitants) were 14 (3‐54), whereas severe cases were 31 (10‐112). Both the number of deaths and that of severe cases showed a significant correlation ( R 2 .57 and .41, with P < .01) with the P/T ratio. Deaths and severe cases were associated with higher mean personal income and lower density of General Practioners (GPs). The association of P/T with severe cases and deaths retained statistical significance after adjusting for mean personal income ( R 2 .30 and .41, respectively; both P = .04) and GPs density ( R 2 .21 and .19, respectively; both P = .03). Conclusions: A more aggressive screening strategy for SARS‐Cov‐2, was associated with lower rates of death and severe disease in Regions of Italy.